Pemanfaatan "SKIMSA" sebagai Pupuk Organik Cair: Pengaruhnya Terhadap Jumlah Helai Daun dan Berat Tanaman Kangkung Darat (Ipomoea reptans) - Lukas Tri Kurniawan; Siti Hani Istiqomah; Sri Muryani (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Waste is a consequence of human activities. The increase of human population and economicgrowth can cause problem in waste handling, especially those containing organic ingredients.This kind of waste, if is just dumped and not appropriately managed will invite animal vectorscarrying disease agents as well as disturb the aesthetic values. This study utilized vegetablewastes and coconut fibre wastes dumped by sellers as liquid organic fertilizer (which are called“Skimsa”) fo Ipomoea reptans. This study was aimed to determine whether the spraying of“Skimsa” and organic liquid fertilizer brand "X", which are sold in the market, give different effecton the leaf number and the weight of that plant, by conducting a quasi experiment followingpost test only with control group design. There were 30 polybags for each treatment group andthe fertilizers were given in four weeks. The data from observation were analysed by usingindependent t-test at 95 % confidence level, and the results showed that the average number ofleaf (p-value=0,063) and the weight (p-value=0,18) of Ipomoea reptans yielded from both organic fertilizers were not significantly different. Therefore, it can be concluded that liquid organicfertilizer made of vegetable waste and coconut fibre waste has same effectiveness with that ofbrand "X".